Creating new filtering system for water purification from various types of contamination in country houses; Химия и химическая технология в XXI веке; Т. 2 - Mosolkov A. Yu. (Химия и химическая технология на иностранном языке Chemistry and Chemical Engineering, in English, 2013)
Заглавие с титульного экрана